2015
DOI: 10.1080/17451000.2015.1024133
|View full text |Cite
|
Sign up to set email alerts
|

First observation of the marine tardigradesBatillipes mirusandBatillipes noerrevangi(Arthrotardigrada, Batillipedidae) from a strongly brackish part of the Polish Baltic Sea coast

Abstract: The tardigrade fauna of Poland is one of the better known in Europe. However, almost all studies have been carried out on the limno-terrestrial species, while marine Tardigrada have been neglected. To the best of our knowledge only one report on marine Tardigrada for Polish waters has been published up to now. In the present study the first records of two marine arthrotardigrade species, Batillipes mirus and Batillipes noerrevangi, from Puck Bay (Baltic Sea) are reported. The lowest salinity value in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…This protein family is conserved widely in Tardigrada, even in Batillipes sp., a non-anhydrobiotic heterotardigrade species. Although this intertidal marine inhabiting Batillipes is not capable of anhydrobiosis, it is capable of surviving short periods of high and low levels of salinity and inhabiting brackish regions [ 57 , 58 ], suggesting tolerance against fluctuations in osmolarity. Such fluctuations would induce physiologies partly mirroring anhydrobiosis.…”
Section: Discussionmentioning
confidence: 99%
“…This protein family is conserved widely in Tardigrada, even in Batillipes sp., a non-anhydrobiotic heterotardigrade species. Although this intertidal marine inhabiting Batillipes is not capable of anhydrobiosis, it is capable of surviving short periods of high and low levels of salinity and inhabiting brackish regions [ 57 , 58 ], suggesting tolerance against fluctuations in osmolarity. Such fluctuations would induce physiologies partly mirroring anhydrobiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Polish tardigrades have been conducted for more than a century (Minkiewicz, 1914;Jakubski, 1915), and up to now, 102 species have been reported from this country (e.g., Kaczmarek, 2008;Kaczmarek et al, 2010;Zawierucha et al, 2015). However, the most comprehensive account on this subject so far is that of Dastych (1988).…”
mentioning
confidence: 99%
“…Despite the interesting biological information that they can provide (de Zio grimaldi & gallo D'Addabbo 2001;Faurby et al 2011Faurby et al , 2012, biogeographical studies on marine tardigrades, and especially on Batillipes, are scarce, often restricted to generalist lists (e.g., Kaczmarek et al 2015;Miller & Perry 2016) and sometimes leading to contradictory interpretations. Actually, results of recent studies suggested that geographic / ecological factors can act as barriers, promoting speciation (e.g., Faurby et al 2011Faurby et al , 2012Zawierucha et al 2015;Faurby & Barber 2015) contrary to hypotheses in favour of wide-ranging species (e.g., hummon 1994). Therefore, further studies in new habitats such as different depths (e.g., hansen 2005), diverse environmental gradients (e.g., Pollock 1970bPollock , 1989Kristensen & Mackness 2000;Faurby et al 2012) or types of substrates (e.g., Rubal et al 2016), would enhance our understanding of tardigrade distribution, and, particularly, could be pivotal to our understanding of the biogeography of the genus Batillipes.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties are increased by the small number of taxonomic characters available and by the marked variability observed in some characters (e.g., McKirdy 1975;gallo D'Addabbo et al 2000). on the other hand, the use of morphometric data for taxonomic purposes must be carefully used because measurements can be biased by specimen orientation or by the physical slide mounting processes (see Mcginty & higgins 1968;Pollock 1971;Kristensen 1978;Morone De Lucia et al 1988;Villora-Moreno & de Zio grimaldi 1993;gallo D'Addabbo et al 2000;Kristensen & Mackness 2000;Zawierucha et al 2015;Fontoura et al 2017;Santos et al 2017). For these reasons, some of the old descriptions of species of Batillipes are incomplete and they may represent complexes of similar species, e.g., cosmopolitan B. mirus and B. pennaki as suggested by Zawierucha et al (2013Zawierucha et al ( , 2015.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation